Efeito antitumoral e antiangiogênico de uma fosfolipase A2 da peçonha de Bothrops jararacussu (BthTX-II) e inibição da Transição Epitélio-Mesênquima (EMT) sob células tumorais de mama - Azevedo, Fernanda Van Petten de Vasconcelos (2019)
Phospholipases A2 represent an enzyme superfamily widely distributed in living organisms, with a broad spectrum of pharmacological activities and therapeutic potential. In this context, the present paper reports firsthand the antitumor, antimetastatic and antiangiogenic effects of BthTX-II, a PLA2 Asp49 isolated from Bothrops jararacussu venom, on breast cancer strains. BthTX-II-induced cell death by modulating different genes of the intrinsic (BAD, BAX, BCL2, and BCL2L1) and extrinsic (TNF, TNFRS10B, TNFRSF1A and Caspase 8) signaling pathways. PLA2 also inhibited cell proliferation, adhesion, migration, cell invasion and 3D growth in matrigel, reducing the aggressiveness of metastatic breast cancer cells by negatively modulating the BRCA1 and BRCA2 tumor suppression genes, as well as the proangiogenic factor. ANGPT1. Also, BthTX-II reduced the expression of vimentin, TWIST1, CK-5 and was able to increase the protein expression of E-cadherin and its gene (CDH-1), leading the metastatic breast cancer cell to assume a characteristic epithelial phenotype with less invasive properties. Interestingly, BthTX-II inhibited human endothelial cell adhesion, invasion, and migration and blocked angiogenesis by decreasing the formation of new vessels in HUVEC cells (in vitro) and the formation of cell extensions in an ex vivo aortic fragment model, as well as reducing production of endothelial growth factor (VEGF). Besides, it demonstrated action on growth in co-culture, whose action was the reduction of tumor mass in vivo in the membrane assay (CAM) in chicken embryos. Taken together, the results show that BthTX-II has significant antitumor and antiangiogenic activity, enabling its use as a potential prototype for the development of antitumor drugs in triple-negative breast cancer therapy.